A rare cause of sciatica: Sciatic nerve schwannoma: Report of one case with long subclinical course and misleading presentation - Maes, Renaud (SICOT J, 2020)
The authors report one case of schwannoma located in the sciatic nerve, just above the popliteal fossa. A sciatic localization is rare, observed in 1% of the patients. The misleading clinical presentation of this localization causes a delay in diagnosis. Magnetic Resonance Imaging (MRI) is the imaging modality of choice, but the final diagnosis is made by the histological examination of the tumor. Schwannoma should be surgically removed without division of the nerve trunk.